Complication occurs after odontectomy of mandibular third molar - Busra, Dicca Neldi; Karasutisna, Tis; Yuza, Abel Tasman (Universitas Padjadjaran, 2012)
Introduction: The average age for completely eruption of the mandibular third molar is age 20-25. The eruption of mandibular third molar sometimes prevented by several factors, caused this tooth becomes impacted. All impacted third molar should be removed with minor surgery, which called odontectomy. Several complications and complaint are accompanied with extraction of impacted third molar. The purpose of this study was to determine the prevalence rate of complications post-odontectomy of mandibular third molar, based on genders, age of the patients, the classification of impactions, and the day of postoperative control. Methods: The characteristics of this study was a descriptive survey that collected the secondary data from the medical records, which used the research papers to collect the data. Results: The results of this study show that there are 545 medical records of the patient included to the study, 62.7% complications occur in women. Complications often occur in age groups over 30 years (56.3%). Conclusion: Most of complications occur in C position in class I, II, and III of Pell and Gregory classification. The most complications is oedem on the first day after surgery (43.1%) and on the day of sutures opened (12.3%).